Routledge handbook of cultural sociology
1 online resource.
Keywords: The thoroughly revised and updated second edition of the Routledge Handbook of Cultural Sociology provides an unparalleled overview of sociological and related scholarship on the complex relations of culture to social structures and everyday life. With 70 essays written by scholars from around the world, the book brings diverse approaches into dialogue, charting new pathways for understanding culture in our global era. Short, accessible chapters by contributing authors address classic questions, emergent issues, and new scholarship on topics ranging from cultural and social theory to politics and the state, social stratification, identity, community, aesthetics, and social and cultural movements. In addition, contributors explore developments central to the constitution and reproduction of culture, such as power, technology, and the organization of work. This handbook is essential reading for undergraduate and postgraduate students interested in a wide range of subfields within sociology, as well as cultural studies, media and communication, and postcolonial theory.